Pemanfaatan Puding Kelor untuk Pencegahan Kekurangan Energi Kronik pada Ibu Hamil dalam Mendukung Persalinan dan Nifas Berkualitas - Sari, Lili Purnama; Irnawati, Irnawati (Kolaborasi: Jurnal Pengabdian Masyarakat, 2026)
Introduction: Chronic Energy Deficiency (CED) in pregnant women remains a significant health problem that can increase the risk of anemia, complications during pregnancy, and poor birth outcomes. Moringa leaves are a locally available nutrient-dense food source that can be processed into various products, including pudding, to help improve nutritional intake among pregnant women. However, limited knowledge and low utilization of moringa leaves in daily nutrition practices highlight the need for community-based education and practical training. Objective: The purpose of this service was to improve the knowledge and skills of pregnant women in preventing CED through nutrition education and practical training on processing moringa leaves into pudding. Method: This public service was conducted by providing health education and a hands-on demonstration of moringa leaf pudding preparation. The activity was carried out at the Bara-Baraya Health Center involving 15 pregnant women with CED as participants. The program consisted of education on balanced nutrition during pregnancy, discussion on the nutritional benefits of moringa leaves, and practical cooking sessions. Skills were evaluated using an observation checklist covering preparation, processing, and hygienic serving steps. Result: The activity resulted in a 95% increase in participants' knowledge after the education session. Pregnant women demonstrated strong enthusiasm and active participation during the demonstration process. They showed improved understanding of the nutritional benefits of moringa leaves, including their content of iron, vitamins, protein, and minerals that support fetal growth and maternal health. Participants also expressed interest in preparing moringa pudding at home as an affordable and nutritious food option. Conclusion: Education and practical training on moringa pudding preparation effectively increased the knowledge and skills of pregnant women in preventing CED. The program is expected to encourage sustainable use of moringa leaves as a local nutritional resource. Follow-up actions include distributing moringa seeds to participants to support independent cultivation and continuous utilization for daily nutrition.